2020
DOI: 10.1371/journal.pone.0228903
|View full text |Cite
|
Sign up to set email alerts
|

Structural differences between REM and non-REM dream reports assessed by graph analysis

Abstract: Dream reports collected after rapid eye movement sleep (REM) awakenings are, on average, longer, more vivid, bizarre, emotional and story-like compared to those collected after non-REM. However, a comparison of the word-to-word structural organization of dream reports is lacking, and traditional measures that distinguish REM and non-REM dreaming may be confounded by report length. This problem is amenable to the analysis of dream reports as non-semantic directed word graphs, which provide a structural assessme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 41 publications
(94 reference statements)
0
22
0
Order By: Relevance
“…This approach allows the researcher to examine the overall structure of a graph, quantifying the pairwise relationships among its units and evidencing features that could not be captured by considering only its elements/nodes. Hence, when applied to language processing, graph analysis determines the non-semantic word-to-word structural organization of speech [ 27 ]. While this method could be applied to both written and spoken dream reports, previous studies mainly used it on oral speech samples.…”
Section: Graph Analysis: Exploring the Structural Properties Of Mentation Reportsmentioning
confidence: 99%
See 3 more Smart Citations
“…This approach allows the researcher to examine the overall structure of a graph, quantifying the pairwise relationships among its units and evidencing features that could not be captured by considering only its elements/nodes. Hence, when applied to language processing, graph analysis determines the non-semantic word-to-word structural organization of speech [ 27 ]. While this method could be applied to both written and spoken dream reports, previous studies mainly used it on oral speech samples.…”
Section: Graph Analysis: Exploring the Structural Properties Of Mentation Reportsmentioning
confidence: 99%
“…In healthy subjects, graph analysis of mentation reports was used to investigate potential stage-specific structural properties. Specifically, Martin and colleagues investigated both differences in graph structure between REM and NREM dreams and the relationship between non-semantic graph attributes and dream report length, defined here as the total number of words used to describe a dreaming experience after excluding redundancies, repetitions, interjections, corrections and dreamer’s comments about the mentation [ 27 ]. By analyzing 133 reports collected from 20 participants in controlled laboratory awakenings from REM and N2 sleep, the authors found that REM dream reports were characterized by higher word count and graph connectedness (expressed in terms of LCC and LSC; see Table 1 ) as compared to N2 dreams.…”
Section: Graph Analysis: Exploring the Structural Properties Of Mentation Reportsmentioning
confidence: 99%
See 2 more Smart Citations
“…There appear to be some differences in the content of REM and NREM mentation. REM mentation reports display more connectivity and more convoluted structures than do NREM (Stage II) mentation reports (Martin et al, 2020). In addition, the dream self in REM mentation reports resembles the waking self, whereas the dream self in NREM (slow wave sleep) mentation reports can take various forms, ranging from a thinking agent, through to a passive observer and an entity similar to the waking self (Occhionero et al, 2005).…”
mentioning
confidence: 99%